Two scandium-based coordination polymers: rapid ultrasound-assisted synthesis, crystal transformation, and catalytic properties. Issue 44 (1st November 2021) - Liu, Rui; Jiang, Yansong; Gong, Yiran; Fu, Yu; Shen, Jieyu; Wang, Li; Fan, Yong; Guo, Yupeng; Xu, Jianing
Abstract : Assisted by ultrasound waves, a Sc-based coordination polymer CP 1 was synthesized successfully. With 1 as the precursor, another stable CP 2 can be obtained by single-crystal to single-crystal transformation and 2 exhibited good catalytic activities. Abstract : A scandium-based coordination polymer (Sc-CP), Sc(ox)1.5 (H2 O)2 ·4H2 O (1 ) (H2 ox = oxalic acid), with a two-dimensional (2D) layered structure was prepared by both hydrothermal synthesis and ultrasound-assisted heating methods using glutaric acid as a modulator. Then, the single crystal of 1 as a precursor was transformed into another 2D Sc-CP, Sc(ox)1.5 (H2 O)2 ·H2 O (2 ), by increasing the temperature. Due to the difference in hydrogen bond interactions between the host framework and guest water molecules, 2 showed good tolerance to various solvents, while 1 exhibited poor stability even exposed in air. After activation, 2 could be used as a heterogeneous Lewis acid catalyst for two classic C–C bond formation reactions, the cyanosilylation reaction and Strecker reaction at room temperature, showing excellent catalytic activity and selectivity.